2021
DOI: 10.1002/humu.24308
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and molecular spectrum of QRICH1 associated neurodevelopmental disorder

Abstract: De novo variants in QRICH1 (Glutamine‐rich protein 1) has recently been reported in 11 individuals with intellectual disability (ID). The function of QRICH1 is largely unknown but it is likely to play a key role in the unfolded response of endoplasmic reticulum stress through transcriptional control of proteostasis. In this study, we present 27 additional individuals and delineate the clinical and molecular spectrum of the individuals (n = 38) with QRICH1 variants. The main clinical features were mild to moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…For example, mice knocked out of the VDR had severe colitis and increased intestinal mucosal permeability ( Zhang et al, 2019b ). QRICH1 plays a key role in the unfolded response to endoplasmic reticulum (ER) stress through transcriptional control of protein status, and QRICH1 variants contribute to neurodevelopmental disorders through dysregulation of the ER stress response ( Kumble et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mice knocked out of the VDR had severe colitis and increased intestinal mucosal permeability ( Zhang et al, 2019b ). QRICH1 plays a key role in the unfolded response to endoplasmic reticulum (ER) stress through transcriptional control of protein status, and QRICH1 variants contribute to neurodevelopmental disorders through dysregulation of the ER stress response ( Kumble et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 35 different pathological variants have been described until now, with most predicted as protein-truncating variants [5]. However only 4 individuals with inherited pathogenic variants have been described lately, showing paternal inheritance in 3 cases and 1 of maternal inheritance [5]. This report is of a mother and daughter with VEBRAS, associated with a new variant of the QRICH1 gene, NM_017730.3: c.337C>T; p.(Gln113*).…”
Section: Introductionmentioning
confidence: 91%
“…You et al showed the role of QRICH1 in maintaining tissue homeostasis during pathological conditions such as inflammatory or metabolic disorders [4]. Recently, Kumble et al published a study of 38 cases, summarizing all previously known clinical and genetic information about pathogenic QRICH1 variants [5]. Overall, 35 different pathological variants have been described until now, with most predicted as protein-truncating variants [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted September 30, 2022. ; https://doi.org/10.1101/2022.09.29.22279724 doi: medRxiv preprint family of proteins includes two additional members, ZMYM4, and QRICH1. Variation in QRICH1 (MIM:617387) has been associated with Ververi-Brady syndrome (MIM:617387), which has features including developmental delay, intellectual disability, non-specific facial dysmorphism, and hypotonia among others 36 .…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%